Facilitated crystal handling using a simple device for evaporation reduction in microtiter plates - Barthel, Tatjana (J Appl Crystallogr, 2021)
In the past two decades, most of the steps in a macromolecular crystallography experiment have undergone tremendous development with respect to speed, feasibility and increase of throughput. The part of the experimental workflow that is still a bottleneck, despite significant efforts, involves the manipulation and harvesting of the crystals for the diffraction experiment. Here, a novel low-cost device is presented that functions as a cover for 96-well crystallization plates. This device enables access to the individual experiments one at a time by its movable parts, while minimizing evaporation of all other experiments of the plate. In initial tests, drops of many typically used crystallization cocktails could be successfully protected for up to 6 h. Therefore, the manipulation and harvesting of crystals is straightforward for the experimenter, enabling significantly higher throughput. This is useful for many macromolecular crystallography experiments, especially multi-crystal screening campaigns.